Translation of ionic liquids to be enteric nanoparticles for facilitating oral absorption of cyclosporine A - Kaiheng Liu; Wenjuan Liu; Zirong Dong; Luyu Zhang; Qiuyu Li; Renjie Zhang; Haisheng He; Yi Lu; Wei Wu; Jianping Qi (Wiley, 2023)
Abstract Ionic liquids (ILs) attract more and more interests in improving drug transport across membrane, including transdermal, nasal, and oral delivery. However, some drawbacks of ILs impede the application in oral drug delivery, such as rapid precipitation of poorly soluble drugs in stomach. This study aimed to employ enteric mesoporous silica nanoparticles (MSNs) to load ILs to overcome the shortcomings faced in oral administration. The choline sorbate ILs (SCILs) were synthesized by choline bicarbonate and sorbic acid and then adsorbed in mesopores of MSNs after dissolving cyclosporin A (CyA). MSNs loading SCILs and CyA were coated by Eudragit® L100 to form enteric nanoparticles. The in vitro release study showed that the CyA and SCILs released only 10% for 2 h in simulated gastric fluids but more than 90% in simulated intestinal fluid. In addition, SCILs and CyA were able to release from MSNs synchronously. After oral administration, enteric MSNs loading SCILs were capable of improving oral absorption of CyA significantly and the oral bioavailability of CyA was similar with that of oral Neoral®. In addition, the oral absorption of enteric MSNs was higher than that of nonenteric MSNs, which showed that enteric coating was necessary to ILs in oral delivery. These findings revealed great potential of translation of ILs to be enteric nanoparticles for facilitating oral absorption of CyA. It is predictable this delivery system is promising to be a platform for delivering poorly water‐soluble drugs and even biologics orally.